Analisis Populasi Mikroorganisme Tanah di Lahan Perkebunan Kelapa Sawit Kebun Adolina PT Perkebunan Nusantara IV Regional II - Simanullang, Rolas; Gunawan, Hari (Dinasti Research, 2026)
The population of soil microorganisms is an important indicator in maintaining the biological quality of soil in oil palm plantation ecosystems. Differences in land management zones such as plates, inter-row spaces, and dead grates are thought to affect soil environmental conditions and the dynamics of microorganism populations. This study aims to analyze the population of soil microorganisms in the form of bacteria and fungi in various oil palm land management zones at the Adolina Regional II Plantation of PT. Perkebunan Nusantara IV, Serdang Bedagai Regency, North Sumatra. The study was conducted from June 2025 to February 2026 using a non-factorial Completely Randomized Design (CRD) with three treatments, namely F1K (in plates), F2K (inter-row spaces), and F3K (dead grates), each replicated five times. Soil samples were taken as a composite at a depth of 20 cm and analyzed at the Soil Chemistry and Biology Laboratory of the University of North Sumatra. The parameters observed included the population of soil bacteria and fungi in CFU/g units, as well as supporting parameters in the form of soil pH and organic C content. The results showed that the highest bacterial population was found in the F2K treatment at 4.05 × 10⁷ CFU/g, while the highest fungal population was found in the F3K treatment at 4.75 × 10⁶ CFU/g. The highest C-organic content was found in the dead trellis at 0.90%, indicating a positive relationship between the accumulation of organic matter and increased activity of soil microorganisms. The results of the analysis of variance (ANOVA) showed that the treatment had no significant effect on the bacterial population (p = 0.372) or fungi (p = 0.591). However, descriptively there was a tendency for an increase in the population of microorganisms in the inter-row